The Impact of Sexual Violence on Adolescents with Intellectual Disabilities: A Scoping Review - Dwi Yati; Syisnawati (INKLUSI, 2026)
Adolescents with intellectual disabilities (ID) are at increased risk of sexual violence due to cognitive and communication challenges, dependence on caregivers, and limited access to protective education. However, evidence regarding its impacts and responses remains fragmented. This scoping review aimed to map evidence on the impacts of sexual violence among adolescents with ID, identify intervention approaches, examine systemic barriers, and highlight research gaps. Following the Arksey and O’Malley framework and PRISMA-ScR guidelines, literature was searched in PubMed, Scopus, CINAHL, and ScienceDirect for studies published between 2020 and 2024. Eleven studies met the inclusion criteria. Findings revealed psychological, behavioural, social, and legal consequences, including PTSD, anxiety, behavioural dysregulation, and barriers to disclosure and support. Educational and community-based interventions showed promise, although evidence was limited by methodological weaknesses and the lack of long-term evaluation. Further trauma-informed interventions and rigorous research are needed. Abstrak Remaja penyandang intellectual disability (ID) berisiko lebih tinggi mengalami kekerasan seksual akibat keterbatasan kognitif, kesulitan komunikasi, ketergantungan pada pengasuh, dan terbatasnya akses terhadap pendidikan perlindungan serta layanan dukungan. Namun, bukti mengenai dampak dan respons yang efektif masih terfragmentasi. Kajian ini bertujuan memetakan bukti tentang dampak kekerasan seksual pada remaja dengan ID, mengidentifikasi pendekatan intervensi, mengkaji hambatan sistemik, dan menyoroti kesenjangan penelitian. Mengikuti kerangka Arksey dan O'Malley serta pedoman PRISMA-ScR, pencarian literatur dilakukan di PubMed, Scopus, CINAHL, dan ScienceDirect untuk publikasi tahun 2020–2024. Sebelas studi memenuhi kriteria inklusi. Temuan menunjukkan dampak psikologis, perilaku, sosial, dan hukum, termasuk PTSD, kecemasan, disregulasi perilaku, serta hambatan dalam pengungkapan dan akses dukungan. Intervensi berbasis pendidikan dan komunitas menunjukkan potensi, meskipun bukti masih terbatas oleh kelemahan metodologis dan minimnya evaluasi jangka panjang.